Electrode

By supporting platinum on graphite and incorporating paraffin, the electrode addresses metal elution and corrosion issues, achieving stable and efficient electrolytic manganese dioxide production with reduced voltage.

JP2025000948AActive Publication Date: 2025-01-07TOSOH CORP
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2024173974
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-03-30
Filing Date
2024-10-03
Publication Date
2025-01-07
Estimated Expiration
2044-03-05

AI Technical Summary

Technical Problem

Existing electrodes for producing electrolytic manganese dioxide face issues with metal elution and corrosion in high-temperature, sulfuric acid environments, leading to poor product quality and increased electrolytic voltage, while the cathode's role in the process has been overlooked.

Method used

The development of an electrode structure that supports platinum on graphite and incorporates paraffin, with specific conditions for platinum loading and paraffin content, to reduce moisture adhesion and electrolytic voltage without metal elution.

Benefits of technology

The electrode effectively reduces moisture adhesion, prevents metal elution, and lowers electrolytic voltage, enabling stable and efficient production of electrolytic manganese dioxide.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025000948000001
    Figure 2025000948000001
  • Figure 2025000948000002
    Figure 2025000948000002
Patent Text Reader

Abstract

To provide an electrode modified for manufacturing electrolytic manganese dioxide obtained by reducing an electrolytic voltage without falling and elution of metal, even when being immersed in an electrolytic solution of sulfuric acid acidity at high temperature, while reducing an amount of attached liquid when the electrode is raised.SOLUTION: There is provided an electrode containing paraffin, that has a structure in which platinum is supported in graphite.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to an electrode, and more particularly to an electrode for producing electrolytic manganese dioxide, for example, an electrode used in the production of electrolytic manganese dioxide used as a positive electrode active material in manganese dry batteries, particularly alkaline manganese dry batteries. [Background technology]

[0002] Electrolytic manganese dioxide is generally produced by electrolytic oxidation deposition on the anode by passing a current between the anode and cathode in a sulfuric acid-acidic manganese sulfate electrolyte at a temperature close to 100°C. The anode is where the electrolytic manganese dioxide deposition reaction takes place, while the cathode is where the hydrogen evolution reaction takes place, and does not directly affect the quality of the electrolytic manganese dioxide. For this reason, the cathode has not received much attention and has only been studied in the past.

[0003] Graphite is mainly used for the cathode, but copper and steel are also used (Patent Document 1). For example, Patent Document 2 considers a cathode in which graphite is coated with copper. However, when a copper-containing cathode is immersed in a high-temperature electrolyte containing sulfuric acid, copper dissolves into the electrolyte when no current is applied. Furthermore, in electrolysis at a temperature close to 100°C with sulfuric acid acidity, even corrosion-resistant metals such as titanium and stainless steel corrode when no current is applied. On the other hand, cathodes for salt electrolysis or water electrolysis (Patent Documents 3 and 4) are not designed for use at a temperature close to 100°C with sulfuric acid acidity. Therefore, these electrodes use elements that may affect the quality of manganese dioxide, and are difficult to use as cathodes for manganese dioxide electrolysis because of their high manufacturing costs.

[0004] Incidentally, during the production of electrolytic manganese dioxide, the electrolyte is kept at a high temperature of 93°C to 98°C. Therefore, an oil layer with a high boiling point, such as paraffin, is floated on top of the electrolyte to prevent the electrolyte from evaporating. However, since paraffin affects the product quality of electrolytic manganese dioxide, methods for removing paraffin that has been incorporated into electrolytic manganese dioxide and electrolysis methods that prevent paraffin from being incorporated are being investigated (Patent Document 2).

[0005] In addition, electrodes such as cathodes and anodes are inserted and removed from the top of an electrolytic cell or a cleaning cell during electrolysis or cleaning, and the electrolyte or cleaning solution adheres to the electrodes when they are pulled up. Since the electrolyte or the like that adheres to the electrodes is lost, there is a demand to reduce the amount of moisture, such as the electrolyte, that adheres to the electrodes. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] International Publication No. 2000 / 037714 [Patent Document 2] Patent Publication No. 2022-7926 [Patent Document 3] International Publication No. 2020 / 110527 [Patent Document 4] Patent No. 6837342 [Patent Document 5] JP 2001-247987 A Summary of the Invention [Problem to be solved by the invention]

[0007] The present disclosure provides an electrode for producing electrolytic manganese dioxide, which has been modified for the purpose of reducing the electrolysis voltage without causing metal detachment or elution even when immersed in a high-temperature, sulfuric acid acidic electrolyte, and which has a small amount of moisture attached when pulled out from an aqueous solution. [Means for solving the problem]

[0008] In this disclosure, we have focused on the performance expression and metal elution of electrodes for producing electrolytic manganese dioxide, and have investigated the modification of the electrodes. As a result, we have found that the amount of moisture attached when the electrode is pulled up is reduced by including paraffin, and that the bath voltage during electrolysis does not increase even under high-temperature and high-concentration sulfuric acid acidic conditions by supporting platinum on graphite.

[0009] That is, the present invention is as defined in the claims, and the gist of the present disclosure is as follows. [1] An electrode consisting of platinum supported on graphite and containing paraffin. [2] The electrode according to the above [1], wherein the electrode is an electrode for producing electrolytic manganese dioxide. [3] The amount of platinum supported per unit area of ​​the graphite is 3 μg / cm 2 More than 500μg / cm 2 The electrode according to the above [1] or [2], [4] The electrode according to any one of the above [1] to [3], wherein the paraffin content is 1 mg / g or more and 100 mg / g or less based on the weight of a portion of the electrode immersed in the electrolyte during electrolysis. [5] The electrode according to any one of the above [1] to [4], wherein the paraffin has a melting point of 40°C or higher and 80°C or lower. [6] The electrode according to any one of the above [1] to [5], wherein the contact angle of the electrode surface with pure water is greater than 90° and less than 180°. [7] A method for producing electrolytic manganese dioxide, using the electrode according to any one of [1] to [6]. [8] A method for producing an electrode according to any one of the above [1] to [6], comprising: a platinum supporting step of supporting platinum on graphite to obtain platinum-supported graphite; and a paraffin-containing step of contacting the platinum-supported graphite with paraffin to cause the platinum-supported graphite to contain paraffin. [9] The method for producing an electrode according to the above [8], wherein in the platinum supporting step, the method for supporting platinum on graphite is a plating method.

[10] The method for producing an electrode according to the above [8], wherein the paraffin-containing step comprises adhering paraffin to a surface of the platinum-supported graphite and then allowing the paraffin to penetrate into the inside of the platinum-supported graphite. Effect of the Invention

[0010] According to the present disclosure, it is possible to provide an electrode for producing electrolytic manganese dioxide, which is modified for the purpose of reducing the amount of moisture adhering when pulled up from an aqueous solution, and reducing the electrolysis voltage without metal falling off or elution even when immersed in a high-temperature sulfuric acid acidic electrolyte. Furthermore, the electrode of the present disclosure does not cause metal elution from the electrode plate into the electrolyte even when no current is applied during electrolysis in the production of manganese dioxide, and can further reduce the electrolysis voltage. In addition, since the amount of liquid adhering when pulled up from an electrolytic bath or a cleaning bath can be reduced, electrolytic manganese dioxide can be produced efficiently and stably. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The present disclosure will be described in detail below with reference to an example of an embodiment thereof. Note that the present disclosure includes any combination of the configurations and parameters disclosed herein, and also includes any combination of the upper and lower limits of the numerical values ​​disclosed herein. <Electrode> The electrode of this embodiment has a structure in which platinum is supported on graphite and contains paraffin, i.e., an electrode containing platinum-supported graphite and paraffin. Furthermore, the electrode of this embodiment can be regarded as an electrode having a graphite base material on which platinum is supported and containing paraffin, or further as an electrode having a graphite base material on which platinum is supported and containing paraffin.

[0012] Graphite is the electrode substrate of the electrode of this embodiment.

[0013] The type of graphite may be, for example, one or more selected from the group consisting of natural graphite, artificial graphite, carbon black, pyrolytic graphite, and carbon fiber, with artificial graphite being preferred from the viewpoints of availability and ease of processing.

[0014] The shape of the graphite may be any shape that can be used as an electrode for producing electrolytic manganese dioxide, and examples of the shape include a plate shape and a rectangular parallelepiped shape that are also used in metal refining and plating, but the shape is not essentially limited to these. Preferred examples of the shape of graphite include a rectangular parallelepiped (columnar) and a plate shape.

[0015] Platinum is a catalyst for the electrolytic oxidation reaction in the production of electrolytic manganese dioxide. The platinum may be any platinum that functions as a catalyst, and may be, for example, one or more selected from the group consisting of metallic platinum, platinum alloys, and platinum compounds. Platinum is preferably metallic platinum, since it can further reduce the bath voltage during the production of electrolytic manganese dioxide.

[0016] A platinum alloy is a metal containing platinum and a metal element other than platinum, and examples of such metals include platinum (Pt) and one or more elements selected from the group consisting of silver (Ag), gold (Au), cobalt (Co), copper (Cu), iron (Fe), iridium (Ir), manganese (Mn), nickel (Ni), palladium (Pd), ruthenium (Ru), titanium (Ti), and zirconium (Zr).

[0017] The platinum compound is a compound containing platinum and a nonmetallic element, such as a compound containing platinum (Pt) and one or more elements selected from the group consisting of carbon (C), chlorine (Cl) and oxygen (O).

[0018] The electrode of this embodiment has a structure in which platinum is supported on graphite, and in particular, platinum is supported on the graphite surface. The structure is that platinum is supported on the graphite surface, that is, the electrode substrate. By having platinum supported on graphite, the bath voltage during the production of electrolytic manganese dioxide can be reduced. It can be reduced.

[0019] In the electrode of this embodiment, platinum may be supported on the portion of the graphite where the electrolytic reaction of electrolytic manganese dioxide occurs, and platinum may be supported on a part or all of the graphite surface. Since the amount of platinum, which is a precious metal, used can be reduced, it is preferable that a part of the graphite surface is supported by platinum. In other words, the graphite may have a region where platinum is supported and a region where platinum is not supported.

[0020] Platinum acts as an electrode catalyst by being present on graphite and maintaining electrical contact with it. It is known that platinum's hydrogen evolution electrode catalytic activity is superior to that of carbon, the material from which graphite is made. For example, the minimum hydrogen evolution overvoltage under 2N sulfuric acid aqueous solution conditions is 335mV for carbon and 0.002mV for platinum. Therefore, compared to graphite, platinum shows superior catalytic activity at a low hydrogen overvoltage.

[0021] The graphite in the electrode of this embodiment has a platinum carrying amount per unit area (hereinafter, simply referred to as "platinum carrying amount") of 3 μg / cm 2 More than 500μg / cm 2 Preferably, it is 10 μg / cm or less. 2 More than 400μg / cm 2 Less than 20 μg / cm is more preferable. 2 More than 200μg / cm 2 The following is even more preferable. When the amount of supported platinum is within the above range, the supported metal (i.e., platinum) does not fall off even under high temperature and high concentration sulfuric acid conditions, and the bath voltage during electrolysis in the production of electrolytic manganese dioxide can be reduced.

[0022] In this embodiment, the amount of platinum supported can be calculated from the following formula using a composition obtained by pulverizing and dissolving in acid the platinum-supported region of the electrode sample and analyzing the solution by inductively coupled plasma optical emission spectrometry (ICP method).

[0023] G=M / A G is the platinum loading (μg / cm 2 ), M is the amount of platinum (μg) determined from the platinum concentration of the solution obtained by ICP measurement, and A is the area (cm2) of the region where platinum is supported in the electrode sample. 2 ).

[0024] The ICP method may be performed using a general inductively coupled plasma emission spectrometer (for example, trade name: OPTIMA3000DV, manufactured by PERKIN ELMER).

[0025] The dissolving solution may be prepared by a known method capable of dissolving the electrode sample, such as a method in which the platinum-supporting region of the electrode is crushed, the electrode sample is heated in an air atmosphere at 400°C to 700°C, a mixed solution of concentrated sulfuric acid and concentrated nitric acid is added to the electrode sample in an air atmosphere, and the mixture is heated to evaporate and dry, and then the dried product is dissolved in aqua regia.

[0026] The electrode of this embodiment contains paraffin. By containing paraffin, the amount of liquid adhering to the electrode of this embodiment when it is pulled up from an electrolytic bath or a cleaning bath can be reduced. The paraffin is a mixture of hydrocarbons mainly composed of linear hydrocarbons having 16 to 40 carbon atoms, and is preferably the same as that used for preventing evaporation of a manganese dioxide electrolytic bath (i.e., preventing evaporation of an electrolyte involved in the production of electrolytic manganese dioxide). In order to prevent evaporation, it is preferable that the paraffin becomes liquid during electrolysis and becomes solid at room temperature during recovery. Therefore, it is preferable that the melting point of the paraffin is 40° C. or more and 80° C. or less, that is, the paraffin has a melting point of 40° C. or more and 80° C. or less, and furthermore, the paraffin has a melting point of 50° C. or more and 65° C. or less. A specific example of paraffin is Paraffin Wax-125 (manufactured by Nippon Seiro Co., Ltd.; melting point 53° C.).

[0027] The content of paraffin is preferably 1 mg / g or more and 100 mg / g or less, more preferably 3 mg / g or more and 80 mg / g or less, and even more preferably 3 mg / g or more and 50 mg / g or less, relative to the mass (unit mass) of the part immersed in the electrolytic solution in the production of electrolytic manganese dioxide using the electrode of this embodiment (hereinafter, also referred to as the "immersed part"). When the content of paraffin is within the above range, the amount of moisture (amount of attached liquid) is reduced. As long as it does not interfere with platinum support (i.e., within the range where platinum can be supported), paraffin may be contained in the graphite before platinum support, or may be impregnated into the electrode after platinum support.

[0028] In this embodiment, the content of paraffin is the mass of paraffin relative to the weighed mass (g) of the electrode of this embodiment.

[0029] The unit moisture content of the electrode of this embodiment is 0 mg / cm 2 More than 4.0mg / cm 2 Less than or equal to 0 mg / cm is preferable. 2 More than 3.0mg / cm 2 Less than or equal to 0 mg / cm is more preferable. 2 More than 2.5mg / cm 2 The following is even more preferable. When the unit moisture adhesion amount is within the above range, the amount of liquid adhered to the electrode of the present embodiment when it is removed from the electrolytic bath or cleaning bath can be reduced, and loss of the electrolytic solution and cleaning solution can be reduced.

[0030] In this embodiment, the unit moisture adhesion amount is calculated by dividing the mass difference before and after immersion of the electrode in pure water by the surface area (cm 2 ) and the value (mg / cm 2 When the graphite has a region where platinum is not supported, the region may be masked and then immersed in pure water.

[0031] The contact angle of the electrode of this embodiment is preferably more than 90° and less than 180°, more preferably 95° or more and less than 180°, and even more preferably 100° or more and less than 180°. When the contact angle exceeds 90°, the amount of liquid adhering to the electrode of this embodiment when it is removed from the electrolytic bath or cleaning bath can be reduced, and loss of the electrolytic solution and cleaning solution can be further reduced.

[0032] The contact angle in this embodiment is a value determined by the following method.

[0033] That is, using a contact angle meter (e.g., device name: DMo-501, manufactured by Kyowa Interface Science Co., Ltd.) and measurement and analysis software (e.g., FAMAS1, manufactured by Kyowa Interface Science Co., Ltd.), 2.0±0.1 μL of pure water is dropped onto the area carrying platinum at room temperature (25° C.±5° C.). Assuming that the shape of the droplet 60 seconds after dropping is a part of a perfect circle, the contact angle (°) of the electrode with the pure water is measured using the following θ / 2 method. The measurement is performed three times, and the arithmetic average value can be regarded as the contact angle of the electrode of this embodiment.

[0034] Contact angle (°)=2×arctan(h / r) h: Distance from the electrode surface to the top of the droplet (mm) r: Radius of the contact surface between the electrode surface and the droplet (mm) The electrode of this embodiment can be used as a cathode for producing electrolytic manganese dioxide. When a plate-shaped electrode of this embodiment having a height of 250 mm, a width of 200 mm, and a thickness of 10 mm is used as a cathode, the voltage in electrolysis under the following conditions (hereinafter also referred to as "bath voltage") is preferably 1.23 V or more and 2.00 V or less, more preferably 1.23 V or more and 1.80 V or less, and even more preferably 1.23 V or more and 1.70 V or less.

[0035] Anode: Titanium electrode (Plate shape: 250mm high, 200mm wide, and 10mm thick) Electrode spacing: 50mm Electrolyte: 85.4g / L manganese sulfate-27.0g / L sulfuric acid mixed aqueous solution 6L and 50g paraffin Electrolyte replenisher: 118g / L manganese sulfate aqueous solution Electrolysis temperature: 96℃ Electrolytic current density: 0.65A / dm 2 Prior to electrolysis, the cathode and anode are placed in an electrolytic cell filled with an electrolyte and paraffin and heated to 96° C. in the order of anode, cathode, and anode, with their main surfaces (height x width surfaces) facing each other, with an interval of 50 mm between them. Then, electrolysis is carried out for 24 hours.

[0036] During electrolysis, the concentration of manganese ions decreases due to the precipitation of electrolytic manganese dioxide accompanying the progress of the electrolytic reaction. In order to maintain a constant manganese ion concentration in the electrolyte, it is preferable to continuously supply an aqueous manganese sulfate solution (electrolyte replenishment solution) to the electrolytic cell during electrolysis, and it is more preferable to supply the aqueous manganese sulfate solution while discharging the electrolyte in an amount equal to the amount of the aqueous manganese sulfate solution supplied. This allows the manganese ion concentration in the electrolyte to be maintained constant.

[0037] The electrode of this embodiment is unlikely to dissolve platinum even when immersed in an electrolytic solution for producing electrolytic manganese dioxide. Therefore, the electrode of this embodiment has a platinum content in a sulfuric acid-manganese sulfate mixed aqueous solution (hereinafter also referred to as "platinum elution amount") after immersing the electrode in the sulfuric acid-manganese sulfate mixed aqueous solution under the following immersion conditions, which may be 0 mg / L or more and 2 mg / L or less, 0 mg / L or more and 1 mg / L or less, 0 mg / L or more and 0.5 mg / L or less, or 0 mg / L or more and 0.1 mg / L or less.

[0038] (Immersion conditions) Electrode shape: Plate shape with height 250 mm, width 200 mm and thickness 10 mm Sulfuric acid-manganese sulfate mixed solution: 6L (Sulfuric acid concentration 27.0g / L) (Manganese sulfate concentration 85.4g / L) Heating start temperature: 86℃ Heating rate: 0.1℃ / min Soaking temperature: 96℃ Soaking time: 80min Furthermore, the electrode of this embodiment is preferably one in which platinum elution is unlikely to occur even when no current is applied after the electrolysis reaction. It is more preferable that the electrode of this embodiment is one in which, after electrolysis under the following electrolysis conditions, the platinum concentration in the electrolyte 3 hours after the electrolysis is stopped (hereinafter, also referred to as "amount of elution without current application") is 0 mg / L or more and 2 mg / L or less, 0 mg / L or more and 1 mg / L or less, 0 mg / L or more and 0.5 mg / L or less, or 0 mg / L or more and 0.1 mg / L or less.

[0039] (Electrolysis conditions) Anode: Titanium electrode (Plate shape: 250mm high, 200mm wide, and 10mm thick) Electrode spacing: 50mm Electrolyte: 85.4g / L manganese sulfate-27.0g / L sulfuric acid mixed aqueous solution 6L and 50g paraffin Electrolyte replenisher: 118g / L manganese sulfate aqueous solution Electrolysis temperature: 96℃ Electrolytic current density: 0.65A / dm 2 Electrolysis period: 6 days By keeping the amount of platinum eluted without current flow within the above range, it is possible to suppress an increase in bath voltage during electrolysis in the production of electrolytic manganese dioxide. Also, by keeping the amount of platinum eluted into the electrolytic solution at the end of the electrolysis within the above range, the life of the electrodes is extended, and electrolytic manganese dioxide can be repeatedly produced.

[0040] The electrode of this embodiment can reduce the electrolysis voltage in the electrolysis reaction using the electrode, and therefore the electrode of this embodiment can be used as an electrode (cathode) for producing electrolytic manganese dioxide, thereby enabling efficient production of electrolytic manganese dioxide. <Electrode manufacturing method> The electrode of the present embodiment can be produced, for example, by using platinum and carrying the precious metal by electroplating or electroless plating in an electrolyte containing precious metal ions using a graphite plate as a working electrode so as to achieve the above-mentioned carrying amount, or by a method for producing an electrode having a paraffin-containing step of causing platinum-supported graphite to contain paraffin. A preferred method for producing the electrode of the present embodiment includes a method for producing an electrode having a platinum-supporting step of carrying platinum on graphite to obtain platinum-supported graphite, and a paraffin-containing step of contacting the platinum-supported graphite with paraffin to cause the platinum-supported graphite to contain paraffin.

[0041] The method for supporting platinum on graphite in the platinum supporting step may be any method capable of supporting platinum on graphite, and is preferably a plating method, more preferably at least one of electroplating and electroless plating, and even more preferably electroplating.

[0042] A preferred electroplating method for supporting platinum on graphite is to use a titanium platinum electrode as the anode, graphite as the cathode, and a mixed solution of chloroplatinic acid (VI) and hydrochloric acid as the plating solution, at a temperature of 50°C to 100°C, and a current density of 0.3 A / dm 2 Above, 2.0A / dm 2Electroplating can be done at temperatures between 60°C and 90°C, and at a current density of 0.5A / dm 2 Above, 1.5A / dm 2 It is preferable to carry out electroplating as follows:

[0043] The longer the electroplating time, the greater the amount of platinum supported. The plating time may be any time depending on the desired amount of platinum supported and the size of the graphite (electrode substrate), and may be, for example, from 15 seconds to 2 minutes.

[0044] In order to prevent the platinum from falling off after plating, it is preferable to polish the graphite prior to supporting platinum.

[0045] After the platinum supporting step, a washing step of washing the platinum-supported graphite may be carried out prior to the paraffin-containing step. The washing step can reduce impurities such as plating solution remaining on the surface. The washing method in the washing step may be any method capable of reducing impurities, and may be a washing method using pure water. A preferred washing method is immersion in warm water at 30°C to 100°C for 10 minutes to 60 minutes, followed by washing with pure water.

[0046] The washed platinum-supported graphite is preferably dried by any method. The drying conditions are arbitrary, but examples include drying in the air at 30° C. to 100° C. for 1 hour to 24 hours.

[0047] The paraffin-containing step is a step of contacting the platinum-supported graphite with paraffin to cause the platinum-supported graphite to contain paraffin.

[0048] The contact between platinum-supported graphite and paraffin may be a method in which paraffin is attached to the surface of platinum-supported graphite and then penetrated into the inside of platinum-supported graphite. For example, a method in which platinum-supported graphite is immersed in pure water having a paraffin layer on the surface and a temperature of 60°C or more and less than 100°C is mentioned, and pure water of 80°C or more and less than 100°C is preferable. The platinum-supported graphite passes through the paraffin layer, so that paraffin is attached to the surface of the platinum-supported graphite, and then, by immersing the platinum-supported graphite in pure water in the above temperature range, the molten paraffin penetrates the platinum-supported graphite. The thickness of the paraffin layer may be a thickness that allows paraffin to be attached uniformly to the surface of the platinum-supported graphite, and may be, for example, 1 cm or more and 2 cm or less. The immersion time is arbitrary, but may be 1 hour or more and 24 hours or less, and is preferably 5 hours or more and 24 hours or less.

[0049] The platinum-supported graphite after the immersion is preferably immersed in warm water not containing paraffin, washed with warm water, and dried, thereby removing the paraffin remaining on the outermost surface of the platinum-supported graphite. EXAMPLES

[0050] The present disclosure will be described below with reference to examples, but the present disclosure is not limited to the following examples.

[0051] <Metal Loading Measurement> The amount of metal carried was measured by measuring the metal concentration in the measurement solution by inductively coupled plasma optical emission spectrometry (ICP method) using a general inductively coupled plasma optical emission spectrometer (product name: OPTIMA3000DV, manufactured by PERKIN ELMER).

[0052] The measurement solution was prepared by the following method. First, a stamp mill was used to pulverize the platinum-supported region of the electrode sample until it passed through a sieve with a mesh size of 0.5 mm. The electrode sample was cut out from the portion immersed in the plating bath described below. That is, the graphite rod (described later) cut out from the bottom to 5 cm (Examples 1 and 2, Comparative Examples 1 to 4), and the graphite plate (described later) cut out from the largest surface (i.e., the surface of height x width, hereinafter also referred to as the "main surface") of the graphite plate (described later) in a range of 2 cm to 6 cm to the right or left and 5 cm above (i.e., a range of 5 cm in height and 4 cm in width) at 4 cm from the bottom end of the graphite plate (Examples 3 to 8, Comparative Examples 5 to 8).

[0053] Next, the crushed electrode sample (fragments) was placed in a magnetic crucible and heated in an air atmosphere at 600°C for 70 hours. 1 mL of concentrated sulfuric acid and 2 mL of concentrated nitric acid were added in the air atmosphere, and the mixture was heated and evaporated to dryness, after which it was dissolved in aqua regia to obtain a solution. Pure water was added until the solution became 1 L to obtain a measurement solution, and the metal concentration of the obtained measurement solution was measured.

[0054] The amount of metal supported was calculated from the metal concentration of the measurement solution obtained by ICP measurement using the following formula.

[0055] G = C × W1 / W2 × V / A In the above formula, G is the metal loading (mg / cm 2 ), C is the metal concentration (mg / L) of the measurement solution obtained by ICP measurement, W1 is the mass (g) of the cut-out electrode sample, W2 is the mass (g) of the crushed electrode sample (pieces), V is the volume of the measurement solution (=1 (L) (0.1 L only in Example 7), and A is the surface area (cm) of the platinum-loaded region of the cut-out platinum-loaded graphite. 2 ).

[0056] <Paraffin content> The paraffin content of the electrode samples was measured by gas chromatography using a gas chromatograph (Agilent 7890A GC, Agilent Technologies, Inc.).

[0057] 1.0 g of electrode sample (fragments) crushed in the same manner as in the measurement of metal loading amount and 5 mL of hexane were added to a screw-top sample tube, and then the tube was shaken for 15 minutes. The tube was then centrifuged at 3000 rpm for 15 minutes, and filtered using a filter (product name: Myshoridisk H-13-5, manufactured by Tosoh Corporation). The hexane layer was collected and used as the measurement sample. The measurement sample was measured by gas chromatography, and the paraffin content was determined by comparing the signal detected by the FID detector attached to the device with the signal of the standard sample.

[0058] As a standard sample, a hexane solution containing paraffin (product name: Paraffin Wax-125, manufactured by Nippon Seiro Co., Ltd.) at a concentration of 10 mg / L was used.

[0059] <Measurement of the amount of metal dissolved into the electrolyte at the start> The amount of metal eluted from the electrode sample into the electrolyte at the start of the test was measured by the ICP method using a general inductively coupled plasma emission spectrometer (product name: OPTIMA3000DV, manufactured by PERKIN ELMER).

[0060] The metal concentration in the diluted electrolyte, which was prepared by diluting the initial electrolyte (described below) 10 times with pure water, was measured by ICP. The metal concentration obtained was multiplied by 10 to obtain the metal concentration (mg / L) in the initial electrolyte.

[0061] <Measurement of moisture adhesion amount and unit moisture adhesion amount> The amount of moisture in the electrode of each Example or Comparative Example was measured by measuring the mass of the electrode before and after immersion in pure water. That is, a screw vial containing pure water was placed on an electronic balance. A rod-shaped electrode was immersed in the screw vial so that the entire electrode surface was immersed in pure water. After immersion for 10 seconds, the rod-shaped electrode was removed from the screw vial. The difference in the values ​​of the electronic balance before and after the electrode was immersed (i.e., the difference between the mass of the rod-shaped electrode before immersion and the mass of the rod-shaped electrode after removal) was calculated and used as the amount of moisture attached (mg).

[0062] The measurement sample used was a rod-shaped electrode with a portion above 5 cm from the bottom covered with PTFE tape.

[0063] The measurement was carried out three times, and the arithmetic mean value was regarded as the amount of moisture adhered (mg).

[0064] The amount of water attached (mg) was then calculated based on the surface area (cm 2 ) to obtain the unit moisture adhesion amount (mg / cm 2 ) was decided.

[0065] Electrode surface area (cm 2 ) is the surface area (cm) of the region where platinum is supported 2 ) was decided.

[0066] <Contact angle measurement> The contact angle of the electrode was measured using a contact angle meter (device name: DMo-501, manufactured by Kyowa Interface Science Co., Ltd.) and the measurement and analysis software provided with the device (FAMAS1, manufactured by Kyowa Interface Science Co., Ltd.). A 2.0±0.1 μL droplet of pure water was dropped onto the electrode surface in an environment at room temperature of 25°C, and the shape of the droplet 60 seconds after the drop was assumed to be a part of a perfect circle, and the contact angle (°) of the electrode with pure water was measured using the following θ / 2 method.

[0067] Contact angle (°)=2×arctan(h / r) h: Distance from the electrode surface to the top of the droplet (mm) r: Radius of the contact surface between the electrode surface and the droplet (mm) The measurement was carried out three times, and the arithmetic mean value was taken as the contact angle (°).

[0068] <Measurement of bath voltage and electrode durability> The bath voltage and electrode durability of the electrodes of each Example or Comparative Example were confirmed by electrolytic synthesis of electrolytic manganese dioxide using an electrolytic cell equipped with a graphite plate of each Example or Comparative Example as a cathode, a titanium plate as an anode, and a manganese sulfate-sulfuric acid mixed aqueous solution as an electrolyte.

[0069] First, 6 L of electrolyte and 50 g of paraffin for preventing evaporation of the electrolyte were added to the electrolytic cell, and the temperature was then raised to 86° C. A manganese sulfate-sulfuric acid mixed aqueous solution with a manganese sulfate concentration of 85.4 g / L and a sulfuric acid concentration of 27.0 g / L was used as the electrolyte.

[0070] Next, one plate electrode (cathode) of each Example or Comparative Example and two titanium plate anodes (height 250 mm, width 200 mm, thickness 5 mm) were immersed in the electrolyte to a depth of 160 mm so as to be perpendicular to the liquid surface of the electrolyte, and then the cathode and anode were fixed at an interval of 50 mm so that their main surfaces (height x width surfaces) faced each other (i.e., in the order of anode, cathode, anode). Then, the electrolyte was heated to 96°C over 3 hours. After the temperature increase was completed, 50 mL of electrolyte was collected (hereinafter, the electrolyte collected after the temperature increase is also referred to as the "initial electrolyte").

[0071] Then, a DC stabilized power supply (PAN-18-10A, Kikusui Electronics Co., Ltd.) was connected and 4.48A (i.e., 0.65A / dm2 to the cathode) was applied. 2 Electrochemical synthesis of electrolytic manganese dioxide was carried out at a constant current of 1000 mA. During electrolysis, an aqueous manganese sulfate solution (electrolyte make-up solution) with a manganese sulfate concentration of 118 g / L was continuously supplied to the electrolytic cell so that the composition of the electrolyte would not change, and the electrolyte was continuously removed from the electrolytic cell so that the amount of electrolyte in the cell was kept constant at 6 L. The voltage display of the DC stabilized power supply was read 24 hours after the start of electrolysis, and this was taken as the bath voltage.

[0072] Electrolysis was continued for another 6 days, and was stopped on the 7th day after the start of electrolysis. 50 mL of electrolyte was collected 3 hours after the electrolysis was stopped (hereinafter, the electrolyte collected 3 hours after the electrolysis was stopped 7 days after the start of electrolysis is also referred to as "final electrolyte"). Furthermore, the amount of metal eluted into the final electrolyte, i.e., the amount of metal eluted without current (mg / L), was measured using the same method as in <Measurement of the amount of metal eluted into the initial electrolyte> above.

[0073] Example 1 All six surfaces of a rectangular (columnar) graphite rod (PSG322, manufactured by SEC Carbon Co., Ltd.) with a length (height) of 100 mm, width of 10 mm, and thickness of 10 mm were polished with sandpaper of grain size #400 (hereinafter, the graphite rod described above that had been polished is also referred to as the "graphite rod"). The area from 50 mm to 70 mm from the bottom of the graphite rod was covered with masking tape for plating (manufactured by 3M Co.) (the area from 50 to 70 mm from the bottom in the length direction was covered).

[0074] Then, the graphite rod was immersed in an electrolyte solution of 10 g / L chloroplatinic acid (VI) and 20 g / L hydrochloric acid at 70°C, and the titanium platinum electrode was used as the anode and the graphite rod as the cathode. 2 For 2 minutes, platinum was supported on the graphite rod (that is, the portion extending from the bottom surface of the graphite rod to 50 mm in the longitudinal direction).

[0075] After the platinum was supported, the masking tape was removed from the graphite rod, which was then immersed in 50°C warm water for 30 minutes, washed with running water, and then dried in air at 50°C for 12 hours. (Hereinafter, the process from covering with masking tape to drying at 50°C is also referred to as the "platinization process.") Thereafter, the electrode was immersed overnight to a height of 6.5 cm from the bottom in a solution of 1.5 cm thick paraffin (product name: Paraffin Wax-125, manufactured by Nippon Seiro Co., Ltd., melting point 53°C) melted in 97°C hot water. After being pulled out of the hot water with the floating paraffin, it was transferred to a beaker filled with hot water at 75°C before the paraffin solidified, and hot water at 75°C was poured over it for 10 minutes to remove the paraffin on the surface. The electrode was then air-dried at room temperature for one day to obtain the electrode of Example 1. (Hereinafter, the process from immersion in the hot water with floating paraffin to air-drying is also referred to as the "paraffin-containing process".) The unit platinum loading is 140μg / cm 2 , paraffin content was 2.9mg / g, moisture content was 41mg, and unit moisture content was 2.0mg / cm 2 , and the contact angle was 124°.

[0076] Example 2 An electrode of Example 2 was obtained in the same manner as in Example 1, except that the electroplating time was 30 seconds.

[0077] The unit platinum loading is 31μg / cm 2 , paraffin content was 4.5mg / g, moisture adhesion was 48mg, and unit moisture adhesion was 2.3mg / cm 2 , and the contact angle was 123°.

[0078] Comparative Example 1 A graphite rod prepared in the same manner as in Example 1 was used as the electrode of Comparative Example 1 (i.e., the same operations as in Example 1 were performed except that the platinum plating step and the paraffin impregnation step were not performed).

[0079] The water adhesion amount of the electrode in this comparative example was 95 mg, and the unit water adhesion amount was 4.5 mg / cm 2 , and the contact angle was 84°.

[0080] Comparative Example 2 A comparative black electrode was prepared by carrying out the same procedure as in Example 1, except that the platinum plating step was not carried out.

[0081] No platinum was detected in this electrode (unit platinum content was 0 mg / g), the paraffin content was 18 mg / g, the moisture content was 44 mg, and the unit moisture content was 2.1 mg / cm 2 , and the contact angle is 113° It was.

[0082] Comparative Example 3 An electrode of Comparative Example 3 was prepared by carrying out the same procedure as in Example 1, except that the paraffin impregnation step was not carried out.

[0083] The unit platinum loading is 140μg / cm 2 No paraffin was detected (paraffin content was 0 mg / g), the moisture content was 95 mg, and the unit moisture content was 4.5 mg / cm 2 , and the contact angle was 81°.

[0084] Comparative Example 4 An electrode of Comparative Example 4 was prepared by carrying out the same procedure as in Example 2, except that the paraffin impregnation step was not carried out.

[0085] The unit platinum loading is 32μg / cm 2 No paraffin was detected, and the moisture content was 110 mg and the unit moisture content was 5.2 mg / cm 2 , and the contact angle was 74°.

[0086] The results of these examples and comparative examples are shown in the table below.

[0087] [Table 1] From the above table, we can see that when paraffin is permeated into graphite, the amount of moisture adhering to the electrode decreases. Furthermore, we can see that for electrodes containing paraffin, the contact angle of pure water increases, and the amount of moisture adhering decreases, regardless of whether or not the electrode is metal-plated and the amount of metal plating.

[0088] Example 3 Using a rectangular parallelepiped graphite plate (PSG322, manufactured by SEC Carbon Co., Ltd., hereinafter also referred to as the "graphite plate") with a height of 250 mm, width of 200 mm, and thickness of 10 mm, the portion of the graphite plate from 160 mm to 185 mm from the bottom was covered with a plating masking tape (manufactured by 3M). Then, the portion from the bottom to 160 mm (160 mm in the height direction from the bottom) was immersed in an electrolyte of 10 g / L chloroplatinic acid (VI) and 20 g / L hydrochloric acid maintained at 70°C, and set so that the two largest surfaces (height x width surfaces; hereinafter also referred to as the "principal surfaces") of the graphite plate faced each other, forming a plating bath with two titanium platinum electrodes as the anode and the graphite plate as the cathode. Using this plating bath, the cathode current density was 1.0 A / dm 2Electroplating was performed for 4 minutes at 40°C, and platinum was supported on the electrode. After that, the masking tape was removed, and the electrode was immersed in 50°C hot water for 30 minutes, washed with running water, and then dried at 50°C for 12 hours. Then, the electrode was immersed overnight in 97°C hot water with 1.5 cm thick paraffin (product name: Paraffin Wax-125, manufactured by Nippon Seiro Co., Ltd., melting point 53°C) floating thereon. The electrode was then pulled out of the hot water with the paraffin floating thereon, and immersed in a container filled with 75°C hot water before the paraffin solidified, and further poured 75°C hot water over it for 10 minutes to remove the paraffin on the surface. The electrode was then air-dried at room temperature for 1 day to obtain the electrode of Example 3.

[0089] The unit platinum loading is 400μg / cm 2 The paraffin content was 44 mg / g, the contact angle was 133°, and the bath voltage was 1.52 V. No platinum was detected in the starting or ending electrolyte, so the amount of platinum eluted and the amount of platinum eluted without current were both 0 mg / L.

[0090] Example 4 An electrode of this example was prepared in the same manner as in Example 3 except that the electroplating time was set to 2 minutes.

[0091] The unit platinum loading is 130μg / cm 2 The paraffin content was 19 mg / g, the contact angle was 114°, and the bath voltage was 1.50 V. No platinum was detected in the starting or ending electrolyte, so the amount of platinum eluted and the amount of platinum eluted without current were both 0 mg / L.

[0092] Example 5 An electrode of Example 5 was prepared in the same manner as in Example 3 except that the electroplating time was set to 1 minute.

[0093] The unit platinum loading is 59μg / cm 2 The paraffin content was 9.4 mg / g, the contact angle was 107°, and the bath voltage was 1.54 V. No platinum was detected in the starting or ending electrolyte, so the amount of platinum eluted and the amount of platinum eluted without current were both 0 mg / L.

[0094] Example 6 An electrode of Example 6 was prepared in the same manner as in Example 3 except that the electroplating time was set to 30 seconds.

[0095] The unit platinum loading is 21μg / cm 2 The paraffin content was 21 mg / g, the contact angle was 112°, and the bath voltage was 1.62 V. No platinum was detected in the starting or ending electrolyte, so the amount of platinum eluted and the amount of platinum eluted without current were both 0 mg / L.

[0096] Example 7 An electrode of Example 7 was prepared in the same manner as in Example 3 except that the electroplating time was set to 15 seconds.

[0097] The unit platinum loading is 3.5μg / cm 2 The paraffin content was 39 mg / g, the contact angle was 115°, and the bath voltage was 1.68 V. No platinum was detected in the starting or ending electrolyte, so the amount of platinum eluted and the amount of platinum eluted without current were both 0 mg / L.

[0098] Comparative Example 5 A graphite plate was used as the electrode of this example (that is, the same operations as in Example 3 were performed except that the platinum plating step and the paraffin impregnation step were not performed).

[0099] No platinum, copper, palladium, or paraffin was detected from this electrode (unit platinum loading, unit copper loading, and unit palladium loading were 0 μg / cm 2 , and paraffin content is 0 mg / g).

[0100] The bath voltage of the electrode of this comparative example was measured, except that no paraffin was added to the electrolytic cell and the electrolyte was not analyzed.

[0101] The contact angle was 84° and the bath voltage was 1.67V.

[0102] Comparative Example 6 The same procedure as in Example 3 was carried out except that the platinum plating step was not carried out, and the graphite plate was impregnated with paraffin to prepare an electrode for Comparative Example 6.

[0103] No platinum, copper or palladium was detected from this electrode (unit platinum loading, unit copper loading and unit palladium loading were 0 μg / cm 2 ), the paraffin content was 48 mg / g, the contact angle was 115°, and the bath voltage was 2.09 V.

[0104] Comparative Example 7 Using the same graphite plate as in Example 3, the area from 160 mm to 180 mm from the bottom of the graphite plate was covered with masking tape for plating (manufactured by 3M), and then the area from the bottom to 160 mm was covered with copper (Cu 2+ The plate was immersed in an electrolyte containing 20 g / L of ions and 40 g / L of sulfuric acid. Two copper plate electrodes were set up facing the two largest surfaces of the graphite plate, and the graphite plate was set as the cathode and the current density was 1.0 A / dm 2 The electrode was electroplated at 50°C for 10 minutes to deposit copper on both sides of the electrode. After that, the masking tape was removed, and the electrode was immersed in 50°C warm water for 30 minutes, washed with running water, and dried at 50°C for 12 hours. The electrode was then subjected to the same paraffin impregnation process as in Example 3 to obtain the electrode of Comparative Example 7.

[0105] The amount of copper supported per unit area on graphite is 1900μg / cm 2 The paraffin content was 36 mg / g, the contact angle was 112°, and the bath voltage was 1.74 V. 22 mg / L and 27 mg / L of copper were detected in the initial and final electrolytes, respectively, so the amount of copper eluted was 22 mg / L and the amount of copper eluted without current application was 27 mg / L.

[0106] Comparative Example 8 Using the same graphite plate as in Example 3, the area from 160 mm to 180 mm from the bottom of the graphite plate was covered with masking tape for plating (manufactured by 3M), and the area from the bottom to 160 mm was immersed in a palladium plating solution (Parabright SST-L, Japan High Purity Co., Ltd.) maintained at 50°C. Two titanium platinum electrodes were set to face the two largest surfaces of the graphite plate as the anodes, and the graphite plate was used as the cathode, with a current density of 1.0 A / dm 2 The electrode was electroplated at 50° C. for 15 seconds to support palladium on both sides of the electrode. After that, the masking tape was removed, and the electrode was immersed in hot water at 50° C. for 30 minutes, then in a 5% hydrochloric acid solution at 50° C. for 5 minutes, and then again in hot water at 50° C. for 30 minutes. The electrode was then washed with running water and dried at 50° C. for 12 hours. After that, the same paraffin impregnation process as in Example 3 was carried out to obtain the electrode of Comparative Example 8.

[0107] The amount of palladium supported per unit area on graphite is 47 μg / cm 2 The paraffin content was 30 mg / g, the contact angle was 126°, and the bath voltage was 1.62 V. No palladium was detected in the starting electrolyte, and 2.8 mg / L of palladium was detected in the ending electrolyte. Therefore, the amount of palladium eluted was 0 mg / L, and the amount of non-current eluted was 2.8 mg / L.

[0108] The performance of graphite electrodes not carrying metal is reduced when they contain paraffin. The results of the above examples and comparative examples are shown in the table below.

[0109] [Table 2] From Comparative Examples 5 and 6 in Table 2, it can be seen that the graphite electrodes containing paraffin and not plated with a metal (platinum, copper or palladium) have an increased bath voltage and a reduced electrode performance.

[0110] However, the bath voltage was reduced by including paraffin and plating a metal (platinum, copper or palladium).Furthermore, it was found from Examples 3 to 7 that the use of platinum as the plating metal could suppress metal elution.

[0111] As described above, the electrode of this embodiment contains paraffin, thereby reducing adhesion of moisture to the electrode, and by supporting platinum, there is no metal elution into the electrolyte even when no current is applied, even in electrolyte conditions that are high temperature and contain sulfuric acid, and has the effect of reducing the voltage during electrolysis.

[0112] Patent Document 3 shows that paraffin permeates graphite and that removing the paraffin improves the performance of the graphite electrode. It has now been discovered that the graphite of the present invention contains paraffin, which has the effect of reducing the amount of liquid that adheres to the electrode when it is pulled up from the liquid.

Claims

1. The graphite has a platinum-supported structure, and the amount of platinum supported per unit area of ​​the graphite is 50 μg / cm 2 More than 500μg / cm 2 The electrode for producing electrolytic manganese dioxide has a contact angle of 100° or more and less than 180° with respect to pure water, and contains paraffin.

2. 2. The electrode of claim 1, wherein said graphite is synthetic graphite.

3. 3. The electrode according to claim 1, wherein the paraffin content is from 1 mg / g to 100 mg / g based on the weight of a portion of the electrode immersed in the electrolyte during electrolysis.

4. 3. The electrode according to claim 1, wherein the paraffin has a melting point of 40° C. or higher and 80° C. or lower.

5. A method for producing electrolytic manganese dioxide, using the electrode according to claim 1 or 2.

6. 3. The method for producing an electrode according to claim 1, further comprising: a platinum supporting step of supporting platinum on graphite to obtain platinum-supported graphite; and a paraffin-containing step of contacting the platinum-supported graphite with paraffin to cause the platinum-supported graphite to contain paraffin.

7. The method for producing an electrode according to claim 6, wherein in the platinum supporting step, platinum is supported on the graphite by a plating method.

8. 7. The method for producing an electrode according to claim 6, wherein the paraffin-containing step comprises attaching paraffin to a surface of the platinum-supported graphite and then allowing paraffin to penetrate into the inside of the platinum-supported graphite.

Citation Information

Patent Citations

  • Device and method for two-step electrolytic hydrogen production based on acidic electrolyte

    CN114059086A

  • JP1973020115B1

  • Gas diffusion electrode

    JP1980028216A

  • Production of cathode for electrolysis of alkali chloride

    JP1980115983A

  • Gas permeable electrode and method of manufacturing

    JP2017206773A